(untitled) - Kazanjian, Kirk (Hoboken, N.J., 2004)
The story behind America's favorite doughnut company and its astounding rise to the top Mention Krispy Kreme and people start licking their lips. Almost everyone has either tasted the company's products or heard about the "secret" recipes involved in making the doughnuts. Making Dough tells the amazing story of Krispy Kreme doughnuts, and reveals the twelve secrets of the company's incredible success. The book traces the history of Krispy Kreme from its inception in 1937 to its present status as an international icon. Filled with interesting anecdotes and fascinating facts, Making Dough tells the compelling true story of a company that has managed to maintain a wholesome, small town image, while achieving phenomenal success through carefully chosen business strategies and alliances. Through interviews with Krispy Kreme executives, franchise owners, employees, and even diehard fans, readers will go behind the counter to learn how a mixture of customer loyalty, high product standards, technological advancements, and community involvement has become a winning business recipe for this popular company. Kirk Kazanjian (Mountain View, CA) is the author of more than fifteen business and personal finance books. A former award-winning television news anchor and reporter, he appears regularly on CNBC, CNN, and Bloomberg TV, and has been featured in a variety of leading publications, including USA Today, BusinessWeek, and Barron's. Amy Joyner (Greensboro, NC) is an award-winning business reporter for the News & Record in North Carolina. She has been covering Krispy Kreme for several years, and has been eating the company's doughnuts her entire life. A former Knight Center fellow, Joyner's stories have appeared in newspapers around the country.
Keywords: Krispy Kreme Doughnuts,Baked products industry; Case studies; United States